Mapping, Monitoring and Assessing Disasters - Mavroulis, Spyridon; Lekkas, Efthymios (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The Special Issue "Mapping, Monitoring and Assessing Disasters" includes recent advances and results from research in the field of disaster detection and monitoring, and disaster impact assessment and mapping. It includes 10 research articles on multiparametric and interdisciplinary research on disaster phenomena related to geophysical and hydrometeorological hazards (e.g., earthquakes, landslides, tsunami, medicanes, megafires) that have occurred in various regions of Greece, New Zealand and Chile. These approaches constitute a useful and effective tool for mapping, monitoring and assessing disasters in areas with similar geodynamic settings and geoenvironmental properties worldwide.